Atrial Failure: What Do We Know About It? - Sidhi Laksono Purwowiyoto; Budhi Setianto; Steven Philip Surya (Interna Publishing, 2022)
Heart failure is the end of all pathological conditions in the heart. Most accepted paradigms in heart failure are always preceded by left ventricle disfunction. Currently, there are several clinical studies that show that heart failure may occur without prior left ventricular dysfunction. Left atrial dysfunction may play a more important role in heart failure than previously expected. Failure of the left atrium can exist independently of left ventricle dysfunction and mitral valve abnormalities. Atrial failure, just like left ventricular failure, can lead to global heart failure. Etiology, pathomechanism and clinical symptoms of atrial failure are complex and not well understood. This review will explain atrial failure.